Meningkatkan Kecerdasan Keuangan Usaha Mikro Bengkel , Tukang Las Desa Sukaharja Bogor - Sianipar, Charles V; Sitio, Raston (Abdi Dharma, 2021)
Realizing the implementation of Tri Dharma Higher Education in the field of Community Service lecturers- lecturers of the Faculty of Economics, Mpu Tantular University in collaboration with the Head of Sukaharja Village carried out community service activities in the form of Real Work Lectures (KKN) Thematic 2021 on Saturday &Sunday, January 16-17, 2021 at the Sukaharja II Kp Elementary School (SD). Cipeuteuy Rt. 002/001, Sukaharja Village Kec. Sukamakmur, Bogor Regency. The number of participants of this activity is one hundred and forty-one participants with details of ten lecturers as resource persons, five small and medium-sized micro enterprises (MSMEs), one BPD, one LPM thirty-six posyandu, thirty-six PKK people, one MUI, one Linmas, Rt thirty-eight people and twelve people from Rw. This activity is divided into two stages with each of the seventy-one participants each counseling while maintaining health protocols. The target of community service is to realize the general community about the importance of financial arrangement and marketing of businesses and especially micro, small and medium enterprises (MSMEs) in the field of culinary or food businesses. The result achieved in community service this time is that the community is getting smarter in managing the finances and marketing of workshop and welding businesses.